Analisis Kelayakan Modul Ekologi Berdasarkan Penilaian Validator dalam Konteks Pendidikan Lingkungan - Hariyati, Astri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to analyze the feasibility of the ecology module based on validator assessments in the context of environmental education. The developed ecology module aims to provide a deep understanding of the importance of environmental protection and to raise ecological awareness among students. The type of research is development research involving validators consisting of content/material experts, language experts, and appearance experts. Data were collected through assessment instruments designed to evaluate the aspects of content, structure, language, and the alignment of the module with environmental education objectives. The research results show that the validation conducted by three expert validators, namely content/material experts at 77.5%, language experts at 82.5%, and appearance experts at 72.5%. The overall average of the three is 79.6%. Overall, the developed ecology module has met the feasibility criteria, although there are some suggestions for improvement regarding the simplification of the material and the use of more engaging media. Based on the validator's assessment, this module is considered effective in conveying ecological concepts and relevant for application in the context of environmental education in schools, thus it can be concluded that the ecology module is deemed feasible and does not need to be revised.